Amino acid functionalized gadofullerene nanoparticles with superior antitumor activity via destruction of tumor vasculature in vivo. (July 2017) - Zhou, Yue; Deng, Ruijun; Zhen, Mingming; Li, Jie; Guan, Mirong; Jia, Wang; Li, Xue; Zhang, Ying; Yu, Tong; Zou, Toujun; Lu, Zhigao; Guo, Jun; et al.
Abstract: Researchers have been puzzled of the therapy of malignant tumors and the current therapeutic strategies are always accompanied by toxicity or side effects. Developing efficient nanodrugs could reduce the dosage and greatly improve the therapeutic effects in cancer treatments. Here we initially reported a novel kind of gadofullerene nanoparticles functionalized with amino acid (β-alanine), which exhibited a superior antitumor activity in hepatoma H22 models via a novel therapeutic mechanism. The involvement of β-alanine improved the tumor inhibition rate up to 76.85% for a single treatment by strengthening the interaction with radiofrequency (RF) and extending blood circulation time. It realized a highly antivascular treatment to cut off the nutrient supply of tumor cells by physically destroying the abnormal tumor blood vessels assisted by RF. In situ and real-time observation of the vascular change was conducted using the dorsal skin fold chamber model, which corresponded to the erythrocyte diapedesis in histopathological examination. The ultrastructural changes of vascular endothelial cells were further investigated by environmental scanning electron microscopy and transmission electron microscopy. Long-term toxicity evaluation showed that the GF-Ala nanoparticles could be eliminated from the mice after several days and no obvious toxicity was found to the main organs. All these encouraging results suggest GF-Ala nanoparticles are valuable for the significant therapeutic potential with high-efficacy and low-toxicity. Graphical abstract: